Penetrating head injury from angle grinder: A cautionary tale - Senthilkumaran, S (Medknow Publications, 2010)
Penetrating cranial injury is a potentially life-threatening condition. Injuries resulting from the use of angle grinders are numerous and cause high-velocity penetrating cranial injuries. We present a series of two penetrating head injuries associated with improper use of angle grinder, which resulted in shattering of disc into high velocity missiles with reference to management and prevention. One of those hit on the forehead of the operator and the other on the occipital region of the co-worker at a distance of five meters. The pathophysiological consequence of penetrating head injuries depends on the kinetic energy and trajectory of the object. In the nearby healthcare center the impacted broken disc was removed without realising the consequences and the wound was packed. As the conscious level declined in both, they were referred. CT brain revealed fracture in skull and changes in the brain in both. Expeditious removal of the penetrating foreign body and focal debridement of the scalp, skull, dura, and involved parenchyma and Watertight dural closure were carried out. The most important thing is not to remove the impacted foreign body at the site of accident. Craniectomy around the foreign body, debridement and removal of foreign body without zigzag motion are needed. Removal should be done following original direction of projectile injury. The neurological sequelae following the non missile penetrating head injuries are determined by the severity and location of initial injury as well as the rapidity of the exploration and fastidious debridement.